Analisa Keputusan Pendanaan dan Struktur Aktiva Terhadap Kinerja Keuangan pada Perusahaan LQ45 - Delima Ramdani; Agus Munandar (Pusat Penelitian dan Pengabdian bagi Masyarakat Politeknik Negeri Tanah Laut, 2026)
The purpose of this study is to provide an understanding of the extent to which financing decisions and asset structure affect the financial performance of LQ45 companies listed on the IDX from 2021 to 2024. Financing decisions are measured by comparing the proportion of debt financing to equity. Asset structure is measured by the difference in the proportion of fixed assets to total company assets. In addition, financial performance is measured using the return on equity formula, which shows net income divided by capital. The purposive sampling research method was chosen for this study. Furthermore, this research uses secondary data as a research data source obtained from audited LQ45 industry financial reports published on the Indonesia Stock Exchange website. The results of this study indicate that asset structure has a negative correlation with financial performance and that financing decisions have no effect on financial performance.